Multi-Modal Image Fusion via Integrated Anisotropic Diffusion in Stationary Wavelet Domain - Bhawna Goyal, Ayush Dogra, Rahul Khoond , Kanav Sharma (International Journal of Advanced Science and Technology, 2020)
CT and MR scans are used in medical imaging to capture the information of targeted organs. Forbetter diagnosis these two models have to be combined into a single frame. Image fusion is atechniqueof generating proficient or interesting information from a set of source images. Fusion method is usedto obtain the maximum information with least information lossin a single image. A new fusion methodis proposed for medical imaging whereanisotropic diffusion is used to exclude source image intoapproximation and detail layer. Guided filter is used to preprocess the excluded source images besidewith the help of stationary wavelet transform and weighted linear superposition final fused image isobtained. Petrovic metrics are applied to access the execution of the proposed method. Theobtainedresults show that purposedmethod outperforms the other state of art method.